An Unusual Laryngeal Foreign Body in Adult: Denture - Deoni Daniswara; Rizka Fakhriani (Universitas Muhammadiyah Surabaya, 2023)
Background: Foreign bodies in the larynx are reported quite rarely, with a prevalence of around 4% among patients, especially geriatrics, and represent an acute airway emergency with significant morbidity and mortality rate. Objective: This case report aimed to provide information on managing the extraction of foreign bodies and the accompanying problems. Discussion: A 49-year-old man with a history of wearing dentures was admitted to the emergency room. The patient complained of a hoarse voice upon waking up, painful swallowing, and a lumpy sensation in his throat, but he had no chest pain, cough, nausea, or vomiting. An indirect laryngoscopy examination revealed a foreign body lodged in the anterior rima glottis, impeding the mobility of the vocal folds. Under general anesthesia, emergency direct laryngoscopy, evacuation, and tracheoscopy were performed. It was observed that a foreign denture body was lodged in the larynx and was evacuated using grasping forceps. Post-evacuation, the vocal folds were swollen, with a false vocal fold hematoma, posterior subglottic laceration, and no active bleeding. Conclusion: Foreign bodies in the larynx must be prompted and gently removed because it leads to life-threatening. In suspected swallowed foreign bodies, plain radiographs are the initial imaging approach. Inhalational or intravenous induction is operated to administer the general anesthetic, along with the maintenance of spontaneous ventilation.